2015
DOI: 10.3390/ijerph121012530
|View full text |Cite
|
Sign up to set email alerts
|

Ag Nanoparticles (Ag NM300K) in the Terrestrial Environment: Effects at Population and Cellular Level in Folsomia candida (Collembola)

Abstract: The effects of nanomaterials have been primarily assessed based on standard ecotoxicity guidelines. However, by adapting alternative measures the information gained could be enhanced considerably, e.g., studies should focus on more mechanistic approaches. Here, the environmental risk posed by the presence of silver nanoparticles (Ag NM300K) in soil was investigated, anchoring population and cellular level effects, i.e., survival, reproduction (28 days) and oxidative stress markers (0, 2, 4, 6, 10 days). The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 41 publications
4
31
0
Order By: Relevance
“…According to Mendes and co-worker, the amount of MT in F. candida treated with AgNPs and AgNO 3 was increased at 48-h exposure and the amount of MT treated with the latter was higher than with the former one [38]. Furthermore, at population level, a dose–response effect of AgNPs is lower than that of AgNO 3 [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Mendes and co-worker, the amount of MT in F. candida treated with AgNPs and AgNO 3 was increased at 48-h exposure and the amount of MT treated with the latter was higher than with the former one [38]. Furthermore, at population level, a dose–response effect of AgNPs is lower than that of AgNO 3 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at population level, a dose–response effect of AgNPs is lower than that of AgNO 3 [38]. The increased amount of MT at cellular level is directly correlated to an up-regulated MTC mRNA and might confirm the toxic effect to F. candida via silver ions released from AgNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Such high concentrations can lead to marked irreversible enzymatic and metabolic changes. Mendes et al (2015), in a similar study but with Folsomia candida (a member of the order Collembola, a common and widespread arthropod that occurs in soils throughout the world), found that the increases in metallothionein and GST > CAT, GR, GSH, and LPO were more marked in those exposed to Ag + than in those exposed to AgNPs.…”
Section: Discussionmentioning
confidence: 94%
“…In an agricultural silt loam soil the EC 50 was estimated >1,855 mg Ag kg −1 for PVP-coated AgNP (Velicogna et al, 2016). With AgNP and LUFA 2.2 soil a dose-response pattern was detected at the concentration range of 64-640 mg Ag kg −1 for F. candida reproduction and the EC 50 was at 540 mg kg −1 (Mendes et al, 2015).…”
Section: Introductionmentioning
confidence: 93%